The Relationship Between Perceived Organizational Support And Work Engagement In The Inpatient Room Of RS X Lamongan - Firas Azhaar Aghnia (Publikasi Indonesia, 2023)
To provide good health services, health workers in a hospital must have good work engagement. Work engagement is defined as a positive, satisfying, work-related state of mind characterized by passion, dedication, and absorption. High-perceived organizational support, employees are more satisfied with their jobs, feel closer to the organization, are more driven to see the goals of the organization as their own, and are more loyal and committed to the organization. To determine the relationship between perceived organizational support and work engagement in nurses and midwives in the Inpatient Installation of X Hospital Lamongan. Research Method: The research design is quantitative observational with cross-sectional analytics. The statistical test uses the Spearman correlation test. The results of the study: there is a relationship between perceived organizational support and work engagement among employees at the Inpatient Installation of X Hospital Lamongan indicated by P <0.05 (0.001 <0.05). In the correlation coefficient, the result is 0.728 which shows that this relationship is strong. Suggestion: the results of this study can be used as information material and input for X Hospital Lamongan.